The Values Compass: Helping athletes act in accordance with their values through functional analysis - Henriksen, K. (Journal of Sport Psychology in Action, 2019)
From a contextual behavioral science perspective, the form of behavior is less important than its context and consequences. Experiential avoidance occurs when athletes` behaviors serve to reduce personal discomfort. Experiential acceptance occurs when athletes are willing to experience their inner life and use this willingness to remain focused on the task at hand. The Values Compass is a model that can be used as a tool for analyzing the function of athletes` behavior. Through a seven-step process, the sport psychology practitioner guides the athletes towards increased awareness, and helps them take steps towards the life they value.